Comparing hemophagocytic lymphohistiocytosis in pediatric and adult patients. Issue 6 (December 2017) - Wysocki, Christian A.
Abstract : Purpose of review: Hemophagocytic lymphohistiocytosis (HLH) has long been thought of primarily as a pediatric disease. However, this syndrome may occur secondary to underlying malignancies, infections, and autoimmune diseases, in adult patients. Here, we seek to highlight similarities and differences between pediatric and adult HLH, knowledge gaps, and areas of active research. Recent findings: Malignancy is a more frequent driver of HLH in adults, present in nearly half. Prognosis is poor as compared with nonmalignant HLH. Prognosis in adults is generally worse than pediatric patients, suggesting that age and other comorbid illnesses not surprisingly affect the outcome of HLH. Diagnostic and treatment approaches are more variable in adults, likely contributing to poorer outcomes. The frequency of mutations in HLH-causing genes is higher than had been anticipated in adults, although with a higher frequency of uniallelic and hypomorphic mutations than in children. Summary: Optimizing diagnostic criteria for earlier detection may benefit both children and adults. Standardizing treatment approaches in adults will be more difficult because of the variability in triggering illnesses, but a more standardized or algorithmic approach will likely be beneficial. More research into the role of uniallelic and hypomorphic mutations in adults is necessary, to understand treatment and prognostic implications.